2005
DOI: 10.1152/ajpregu.00783.2004
|View full text |Cite
|
Sign up to set email alerts
|

Glutamine-dependent inhibition of pial arteriolar dilation to acetylcholine with and without hyperammonemia in the rat

Abstract: Glutamine has been shown to influence endothelial-dependent relaxation and nitric oxide production in vitro, possibly by limiting arginine availability, but its effects in vivo have not been well studied. Hyperammonemia is a pathophysiological condition in which glutamine is elevated and contributes to depressed CO 2 reactivity of cerebral arterioles. We tested thehypothesis that acute hyperammonemia decreases pial arteriolar dilation to acetylcholine in vivo and that this decrease could be prevented by inhibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 35 publications
1
6
0
Order By: Relevance
“…50 Likewise, MSO restored ammonia-induced reduced CBF responsiveness to hypercapnia 51 and depressed vasodilatory response to acetylcholine. 52 Recently, a 1 H-MRS examination revealed a good correlation between cerebral glutamine level (glutamate/ glutamine signal) and the severity of neuropsychological effects induced by hyperammonemia in patients with cirrhosis. 53 Additionally, the brain concentration of glutamine, as measured by microdialysis, almost perfectly correlated with levels of intracranial pressure.…”
Section: Glutamine Is Harmfulmentioning
confidence: 99%
“…50 Likewise, MSO restored ammonia-induced reduced CBF responsiveness to hypercapnia 51 and depressed vasodilatory response to acetylcholine. 52 Recently, a 1 H-MRS examination revealed a good correlation between cerebral glutamine level (glutamate/ glutamine signal) and the severity of neuropsychological effects induced by hyperammonemia in patients with cirrhosis. 53 Additionally, the brain concentration of glutamine, as measured by microdialysis, almost perfectly correlated with levels of intracranial pressure.…”
Section: Glutamine Is Harmfulmentioning
confidence: 99%
“…Astrocytes are enriched in glutamine synthetase which forms glutamine from ammonia and glutamate (22,85). During hyperammonemia, increases in tissue glutamine result in depressed cerebrovascular reactivity to CO 2 and acetylcholine due, in part, to glutamine's interference with NOS activity (46,47,57,86,108). Astrocyte swelling and increased extracellular K + activity related to the osmotic effect of glutamine accumulation may also contribute to impaired vascular reactivity (106,109,116).…”
Section: Astrocyte Function In Pathophysiological Statesmentioning
confidence: 99%
“…Two diverse effects of L-glutamine on vascular reactivity have been observed. In vivo and in vitro studies have shown that L-glutamine influences endothelial-dependent relaxation by inhibiting availability of NADPH (Wu et al 2001) and by inhibiting recycling of citrulline to arginine to limit nitric oxide release (Kawaguchi et al 2005; Arnal et al 1995; Meininger and Wu 1997; Okada et al 2000), whereas other studies have postulated that a longer duration vasodilatory effect of L-glutamine is by its donation of nitrogen molecule for vasodilator synthesis (Xu and Pearl 1994). Thus, we hypothesized that repeated maternal alcohol exposure would lead to: (1) maternal and fetal hypercapnic acidemia; (2) alteration of systemic hemodynamics; (3) a decrease in uterine blood flow; and (4) subsequent changes in fetal regional brain blood flow.…”
Section: Introductionmentioning
confidence: 99%